Effects of Early MSC Intervention on Preventing the Streptozotocin-Induced T1DM Progression in Mice. (29th July 2020) - Zha, Lanlan; Li, Xue; Meng, Xiangyu; Liu, Yuanlin; Liu, Weijiang; Wang, Yang; Fan, Yue; Zhou, Bin; Li, Pei; Zheng, Rongxiu; Zhang, Yi
Abstract : Type 1 diabetes mellitus is characterized by progressive pancreatic β -cells failure and progressive autoimmunity. It is difficult to diagnose T1DM and to prevent the pancreatic β -cells destruction because of the undetectable pancreatic β -cell necrosis and abnormal autoimmunity. Here, we built streptozotocin-induced T1DM mouse model and performed MSC injection at the early stage of T1DM. We found that MSC infusion displayed enhanced effects on reducing the pathological damage and improving the survival quality. Moreover, the delivery of MSCs inhibited Th1 cell polarization and downregulated the Th1 subset ratio. The immunomodulatory mechanism of MSC was further investigated. Real-time PCR and ELISA assays demonstrated that IFN- γ expression at both mRNA and protein level in MSC infusion T1DM mice was downregulated, partially regulated by MSC-exosome-derived miR-148a-3p. Taken together, this early therapeutic strategy may improve the clinical efficacy of MSC-based therapy in T1DM.